Higher Serum Soluble TREM2 as a Potential Indicative Biomarker for Cognitive Impairment in Inadequately Controlled Type 2 Diabetes Without Obesity: The DOR-KyotoJ-1 - Tanaka, Masashi; Yamakage, Hajime; Muranaka, Kazuya; Yamada, Tsutomu; Araki, Rika; Ogo, Atsushi; Matoba, Yuka; Watanabe, Tetsuhiro; Saito, Miho; Kurita, Seiichiro; Yonezawa, Kazuya; Tanaka, Tsuyoshi; et al. (Frontiers in Endocrinology, 2022)
Objective: Type 2 diabetes is a risk factor for dementia. We investigated whether serum levels of soluble triggering receptor expressed on myeloid cell 2 (sTREM2), a soluble form of the cell surface receptor TREM2, were predictive of cognitive impairment in type 2 diabetes without obesity. Methods: A total of 166 Japanese patients with type 2 diabetes without obesity were followed-up for 2 years. We measured clinical parameters, assessed cognitive function using the mini-mental state examination (MMSE), quantified and divided serum sTREM2 levels into quartiles, and examined the longitudinal associations. Results: During the follow-up, HbA1c levels were elevated in 98 patients and decreased in 68 patients. In the HbA1c-elevated group, higher sTREM2 levels at baseline showed a significant association with a greater tendency for reduction in MMSE scores (P for trend = 0.015), whereas they were not significantly associated with other examined parameters. In the HbA1c-decreased group, there was no significant association between sTREM2 levels at baseline and changes in MMSE scores, but higher sTREM2 levels at baseline were significantly associated with a greater tendency for reduction in waist circumference (P for trend = 0.027), homeostasis model assessment of insulin resistance (P for trend = 0.039), and sTREM2 levels (P for trend = 0.023). Conclusions: Glycemic control is suggested to be important in preventing cognitive impairment in patients with type 2 diabetes without obesity. Higher serum sTREM2 levels would be a predictive marker for cognitive impairment in inadequately controlled type 2 diabetes without obesity.